If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(3y + -7) = 5 Reorder the terms: -2(-7 + 3y) = 5 (-7 * -2 + 3y * -2) = 5 (14 + -6y) = 5 Solving 14 + -6y = 5 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + -6y = 5 + -14 Combine like terms: 14 + -14 = 0 0 + -6y = 5 + -14 -6y = 5 + -14 Combine like terms: 5 + -14 = -9 -6y = -9 Divide each side by '-6'. y = 1.5 Simplifying y = 1.5
| 2x+4(7x-10)=110 | | 36=x^2+2x+8 | | A+7=-10 | | 6a-27=-3(2+5a) | | x=vqs | | A+4=-17 | | X=via | | 12x^2-84x+216=0 | | -3(6y-1)+9y=3(y+4) | | A+1=-13 | | 9y^2+1=12y | | 8-1/3x= | | x-30=2x+10 | | log1/5(7) | | 28*3.14159=2r | | -7y=2x+17 | | 28*(pi)=2r | | A+5=-14 | | 0.30x+4.9=0.32x+4.48 | | l=2w+2l | | 110=2x-3 | | 1-8y-5y=79 | | V-4=4 | | 8k^2+79k-10=0 | | 7y=32+3(13.5) | | 6b^2-2=334 | | -13=4x+1-2x | | 4-2(8x+4)=-132 | | -12x^2+16x+2=0 | | (7z/4w^8)*(w/5z) | | -5y-t(-6-2y)=0 | | 7-2x-(1-3x/7)=2-(2x-1/3) |